Supramolecular FRET photocyclodimerization of anthracenecarboxylate with naphthalene-capped γ-cyclodextrin - Wang, Qian; Yang, Cheng; Fukuhara, Gaku; Mori, Tadashi; Liu, Yu; Inoue, Yoshihisa (Beilstein Journal of Organic Chemistry, 2011)
γ-Cyclodextrin (CD) derivatives with a naphthalene moiety anchored to one or two of the glucose units of the CD were synthesized in order to investigate the effects of flexible and rigid capping upon complexation, as well as Förster resonance energy transfer (FRET) and photochirogenic behavior of anthracenecarboxylate (AC) moieties. UV–vis, circular dichroism and fluorescence spectral studies revealed that two AC molecules are simultaneously included in the modified γ-CD cavity to form a right-handed screw and also that the naphthalene cap efficiently transfers the singlet energy to AC included in the CD cavity via the FRET mechanism. Compared to native γ-CD, the modified γ-CDs showed much higher first association constants (K1) but relatively lower second association constants (K2) for AC, leading to two-fold larger overall affinities (K1K2). Photocyclodimerization of AC with these modified γ-CDs produced more head-to-head (HH) dimers in much better enantiomeric excesses (ee) for anti-HH dimer compared to native γ-CD. Interestingly, FRET excitation further enhanced the chemical and optical yields of anti-HH dimer up to 36% and 35% ee, for which the highly efficient FRET sensitization within the CD cavity, minimizing the “contamination” from the achiral “outside” photoreaction, is responsible. FRET sensitization also enabled us to achieve the catalytic photocyclodimerization of AC with a sub-equivalent amount of chiral supramolecular host.
Keywords: anthracenecarboxylic acid; capped γ-cyclodextrin; FRET sensitization; photochirogenesis; photocyclodimerization

(untitled) - Inoue, Y. (Chem. Rev., 1992)

Chiral Photochemistry; Molecular and Supramolecular Photochemistry - Inoue, Y.; Ramamurthy, Y. (Marcel Dekker, 2004)

(untitled) - Griesbeck, A. G.; Meierhenrich, U. J. (Angew. Chem., Int. Ed., 2002)

Cyclodextrin Materials Photochemistry, Photophysics and Photobiology - Yang, C.; Inoue, Y. (Supramolecular Photochirogenesis with Cyclodextrin, 2006)

(untitled) - Inoue, Y. (Nature, 2005)

(untitled) - Bauer, A.; Westkämper, F.; Grimme, S.; Bach, T. (Nature, 2005)

(untitled) - Inoue, Y.; Dong, F.; Yamamoto, K.; Tong, L.-H.; Tsuneishi, H.; Hakushi, T.; Tai, A. (J. Am. Chem. Soc., 1995)

(untitled) - Lu, R.; Yang, C.; Cao, Y.; Wang, Z.; Wada, T.; Jiao, W.; Mori, T.; Inoue, Y. (Chem. Commun., 2008)

(untitled) - Sivaguru, J.; Natarajan, A.; Kaanumalle, L. S.; Shailaja, J.; Uppili, S.; Joy, A.; Ramamurthy, V. (Acc. Chem. Res., 2003)

(untitled) - Aechtner, T.; Dressel, M.; Bach, T. (Angew. Chem., Int. Ed., 2004)

(untitled) - Nishioka, Y.; Yamaguchi, T.; Kawano, M.; Fujita, M. (J. Am. Chem. Soc., 2008)

(untitled) - Nakamura, A.; Inoue, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Wada, T.; Nishijima, M.; Fujisawa, T.; Sugahara, N.; Mori, T.; Nakamura, A.; Inoue, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Nakamura, A.; Inoue, Y. (J. Am. Chem. Soc., 2005)

(untitled) - Nishijima, M.; Wada, T.; Mori, T.; Pace, T. C. S.; Bohne, C.; Inoue, Y. (J. Am. Chem. Soc., 2007)

(untitled) - Yang, C.; Mori, T.; Origane, Y.; Ko, Y. H.; Selvapalam, N.; Kim, K.; Inoue, Y. (J. Am. Chem. Soc., 2008)

(untitled) - Ke, C.; Yang, C.; Mori, T.; Wada, T.; Liu, Y.; Inoue, Y. (Angew. Chem., Int. Ed., 2009)

(untitled) - Yang, C.; Fukuhara, G.; Nakamura, A.; Origane, Y.; Fujita, K.; Yuan, D.-Q.; Mori, T.; Wada, T.; Inoue, Y. (J. Photochem. Photobiol., A: Chem., 2005)

(untitled) - Yang, C.; Nakamura, A.; Fukuhara, G.; Origane, Y.; Mori, T.; Wada, T.; Inoue, Y. (J. Org. Chem., 2006)

(untitled) - Yang, C.; Nakamura, A.; Wada, T.; Inoue, Y. (Org. Lett., 2006)

(untitled) - Yang, C.; Nishijima, M.; Nakamura, A.; Mori, T.; Wada, T.; Inoue, Y. (Tetrahedron Lett., 2007)

(untitled) - Yang, C.; Mori, T.; Inoue, Y. (J. Org. Chem., 2008)

(untitled) - Fujita, K.; Yamamura, H.; Imoto, T.; Fujioka, T.; Mihashi, K. (J. Org. Chem., 1988)

Circular dichroism–principles and applications - Nakanishi, K.; Berova, N. (Wiley-VCH, 2000)